International Trade Activities as Drivers of Economic Growth: Macro Conditions - Francisca Sestri Goestjahjanti; Dewiana Novitasari; Rahmawati (Universitas Negeri Semarang, 2024)
Global economic growth has hovered around 2-3% over the past decade, resulting in stagnant GDP growth for Indonesia at approximately 5%. This research aims to analyze the effects of macroeconomic conditions, specifically money supply (M2), foreign debt, and international trade activities, on Indonesia's GDP growth from 1994 to 2023. Utilizing a linear regression method with 30 observations, the study finds significant impacts of the independent variables on GDP growth. M2 influences GDP growth by 93%, foreign debt by 76.6%, and net exports by 92.3%. Simultaneously, changes in these variables explain 93.7% of the variation in Indonesia's GDP. The theoretical foundation of this research is built upon previous studies on economic growth and macroeconomic factors, emphasizing the role of monetary policy, debt management, and export diversification. The findings indicate that the careful management of M2 is critical to fostering investment and consumption, while excessive reliance on foreign debt may hamper long-term growth. Non-oil and gas exports significantly contribute to GDP, underscoring the importance of export diversification. The study concludes that these macroeconomic factors are vital for sustainable economic growth and improving welfare in Indonesia, and recommends policy interventions to optimize their effects.